'Tell Me What You Eat and I'll Tell You Who You Are': Changing Eating Habits in Cochabamba, Bolivia. (November 2015) - Léon, Rosario
Abstract: This article describes changes in the lives of families in two communities in the Cochabamba Region, Bolivia, caused in part by food price volatility. It questions whether government policy aimed at 'Vivir Bien' (Living Well), is tackling the real issues of ill‐being that arise from the commercialisation of food. Adaptation to a rising cost of living has social, economic and cultural costs for the families. The article illustrates these changes by recovering the voices and views of the community members themselves. These changes are broader, more prolonged, and more complex than the 'Vivir Bien' policy has assumed.